2022
DOI: 10.1371/journal.pone.0276552
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression in Uganda: A systematic review and meta-analysis

Abstract: Background Depression is one of the most studied mental health disorders, with varying prevalence rates reported across study populations in Uganda. A systematic review and meta-analysis was carried out to determine the pooled prevalence of depression and the prevalence of depression across different study populations in the country. Methods Papers for the review were retrieved from PubMed, Scopus, PsycINFO, African Journal OnLine, and Google Scholar databases. All included papers were observational studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 169 publications
1
8
1
Order By: Relevance
“…High levels of depression and anxiety raise concerns about the capacity of mental healthcare systems to respond during the pandemic. The prevalence of depression in this study was higher than national pre-pandemic levels of 29.3% [23]. In addition to studies in the general adult population in Uganda, there is evidence that mental health was significantly affected by the COVID-19 pandemic even when not directly affected by the infection [24].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…High levels of depression and anxiety raise concerns about the capacity of mental healthcare systems to respond during the pandemic. The prevalence of depression in this study was higher than national pre-pandemic levels of 29.3% [23]. In addition to studies in the general adult population in Uganda, there is evidence that mental health was significantly affected by the COVID-19 pandemic even when not directly affected by the infection [24].…”
Section: Discussioncontrasting
confidence: 54%
“…In line with these findings, evidence from the United States (23) showed that experiencing a COVID-19 infection was associated with an increased risk of common mental disorders such as anxiety and depression in the acute phase of the infection. This is also in agreement with multiple other studies reporting an elevation in mental health problems following infection [29][30][31][32].…”
Section: Discussionmentioning
confidence: 56%
“…High levels of depression and anxiety raise concerns about the capacity of mental healthcare systems to respond during the pandemic. The prevalence of depression in among slum dwellers in this study was higher than national pre-pandemic levels of 29.3% [ 40 ]. However, it’s important to note that the national survey had a larger sample and was not specifically focused on slum dwellers.…”
Section: Discussionmentioning
confidence: 91%
“…Anxiety and depression are common responses by people from countries experiencing crisis and war ( 25–28 ). Anxiety levels may be high if people believe that the crisis will continue for a long time ( 28 ); high levels of depression and anxiety have been reported among young people exposed to war in Ukraine ( 23 ); elevated depression and increased tendencies toward alcohol and drug abuse have been reported among university students and personnel from Ukraine ( 29 ); a high prevalence of anxiety and depression has been reported among war refugees ( 15 , 30 , 31 ) and IDP ( 32 ). PTSD is common among people following traumatic experiences like war.…”
Section: Literature Reviewmentioning
confidence: 99%